The Time Traveler's Wife - Niffenegger, Audrey (Orlando : Harcourt, 2004)
Passionately in love, Clare and Henry vow to hold onto each other and their marriage as they struggle with the effects of Chrono-Displacement Disorder, a condition that casts Henry involuntarily into the world of time travel.
Originally published: San Francisco, Calif. : MacAdam/Cage, c2003.
"Harvest reading guide"--P. [4] of cover.
Keywords: Fiction